COMPUTER-BASED EXPLORATION, RESEARCH AND CONTROL OF TV - SENGUPTA CAESAR; WUELLNER TROND THOMAS; KUSCHER ALEXANDER FRIEDRICH (2015)
콘텐츠를 전송하는 방법은, 콘텐츠를 전송하라는 제 1 디바이스로부터의 요청에 응답하여 콘텐츠를 상기 제 1 디바이스로부터 제 2 디바이스로 전송하는 단계, 상기 전송된 콘텐츠를 상기 제 2 디바이스에서 분석하여 전송된 콘텐츠의 타입을 결정하는 단계, 및 상기 전송된 콘텐츠의 결정된 타입에 따라서 상기 전송된 콘텐츠를 제 2 디바이스에서 디스플레이하도록 제공하는 단계를 포함한다. A method for transferring content includes transferring content from a first device to a second device in response to a request from the first device to transfer the content, analyzing the transferred content at the second device, to determine a type of the transferred content and providing the transferred content for display at the second device according to the determined type of the transferred content.